Regime-Dependent Directional Accuracy of Fibonacci Retracement, SMA100, and RSI: A Rule-Based Backtest of Indonesian Consumer Stocks - Putra Aditya Danis Wara Daffa; Alamsyah Alamsyah; Adrianda Anwar (Economy and Finance Enthusiastic, 2026)
Technical indicators are often evaluated as if their performance were transferable across assets and market states, although trend-following, momentum, and retracement rules encode different assumptions. This study evaluates the directional hit rate of Fibonacci retracement, a 100-day simple moving average (SMA100), a 14-day relative strength index (RSI14), and a composite rule for PT Unilever Indonesia Tbk (UNVR), PT Indofood Sukses Makmur Tbk (INDF), and PT Mayora Indah Tbk (MYOR). The supplied archive contains 1,211 synchronized daily closing-price observations from 2 January 2020 to 30 December 2024; the Pine Script evaluation window was bounded from 1 January 2020 to 30 January 2025. Signal correctness was defined by the direction of the next closing price for stand-alone rules and the third subsequent close for the composite rule. Fibonacci hit rates were 38%, 39%, and 52%; SMA100 achieved 63%, 41%, and 44%; RSI14 achieved 42%, 43%, and 80%; and the composite rule achieved 58%, 74%, and 57% for UNVR, INDF, and MYOR, respectively. The composite macro-average (63%) exceeded each stand-alone macro-average, but it underperformed the best stand-alone rule by 5 percentage points for UNVR and 23 points for MYOR. Thus, the apparent benefit of indicator aggregation was concentrated in INDF and cannot be generalized across issuers. The results support regime-conditioned indicator selection rather than indiscriminate signal stacking. Because the rules use different forecast horizons, omit transaction costs, and allow overlapping signals, the reported hit rates measure directional classification—not trading profitability.